Theoretical models of transformational and transactional leadership in the educational context - Haya Yumna Ilmin Auliya; Neneng Aminah; Encep Syarifudin; Machdum Bachtiar (At Turots: Jurnal Pendidikan Islam, 2025)
Modern education faces complex challenges from globalization, digital technology development, and increasing demands for human resource quality that require leadership capable of navigating rapid change and creating an adaptive organizational culture. This study examines the integration of transformational and transactional leadership in the context of education as a response to these complexities. Transformational leadership focuses on changing values, vision, and inspiration through the dimensions of idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Meanwhile, transactional leadership emphasizes the principle of reward and punishment-based exchange to maintain discipline and achieve minimum standards. This study uses a comparative literature review design with a systematic qualitative approach, analyzing journal articles from 2020-2025 from the Google Scholar, ERIC, and Portal Garuda databases. Data analysis was conducted through reflexive thematic analysis in three stages: data familiarization and systematic coding, comparative thematic analysis, and interpretive synthesis using a meta-ethnography approach with the help of NVivo software. The results show that effective transformational leadership creates a dynamic learning culture, increases intrinsic motivation, encourages innovation, and develops social-emotional aspects. Transactional leadership provides operational structure, management efficiency, and the achievement of short-term standards. The integration of both styles creates optimal synergy that balances innovation with organizational stability. Hybrid leadership has been proven to improve teacher performance, job satisfaction, and student academic outcomes, especially in the digital era that demands high adaptability. The study concludes that educational leaders need to develop adaptive skills to apply both approaches situationally to meet the unique needs of educational institutions and achieve sustainable excellence.